Conjugation with Tris Decreases the Risk of Ketoprofen-Induced Mucosal Damage and Reduces Inflammation-Associated Methane Production in a Rat Model of Colitis - Melinda Ugocsai; Anett Bársony; Réka Anna Varga; Ámos Gajda; Noémi Vida; Norbert Lajkó; Benedek Rónaszéki; Gábor Tóth; Mihály Boros; Dániel Érces; Gabriella Varga (Pharmaceutics, 2023)
We have designed a new compound from the non-steroidal anti-inflammatory drug (NSAID) ketoprofen (Ket) and 2-amino-2-(hydroxymethyl)-1,3-propanediol (Tris) precursors, with the aim to reduce the gastrointestinal (GI) side effects of NSAID therapies. We investigated mucosal reactions in a standard rat model of colitis together with methane generation as a possible indicator of pro-inflammatory activation under this condition (approval number: V./148/2013). Whole-body methane production (photoacoustic spectroscopy) and serosal microcirculation (intravital videomicroscopy) were measured, and mucosal damage was assessed (conventional histology; in vivo laser-scanning endomicroscopy). Inflammatory markers were measured from tissue and blood samples. Colitis induced an inflammatory response, morphological colonic damage and increased methane output. Ket treatment lowered inflammatory activation and colonic mucosal injury, but macroscopic gastric bleeding and increased methane output were present. Ket-Tris reduced inflammatory activation, methane emission and colonic mucosal damage, without inducing gastric injury. Conjugation with Tris reduces the GI side effects of Ket and still decreases the inflammatory response in experimental colitis. Methane output correlates with the mucosal inflammatory response and non-invasively demonstrates the effects of anti-inflammatory treatments.